Challenges and Strategies of Shared Decision-making in Clinical Practice - Yecong TANG; Lili ZHUANG; Xiuwen LI; Zhenzhu LIU (Yixue yu zhexue)
Shared decision-making (SDM) is a therapeutic decision-making model that offers numerous benefits in clinical practice. However, there are still some limitations that affect its effectiveness, such as patients' social attributes limiting their ability to participate, time constraints in modern medical work, and the increasing tension in doctor-patient relationships. To enhance medical outcomes, it is essential to foster an effective SDM model by improving healthcare providers' empathy, strengthening doctor-patient communication, and guiding patients to participate appropriately. This approach not only enhances the patient experience, but also serves as a valuable strategy for improving medical professionals' humanistic care abilities.